Factors associated with childhood diarrheal in Ethiopia; a multilevel analysis - Setegn Muche Fenta; Teshager Zerihun Nigussie (BMC, 2021)
Abstract Background Diarrhea is the second cause of child deaths globally. According to World Health Organization reports, in each year it kills more than 525,000 children under-5 years. More than half of these deaths occur in five countries including Ethiopia. This study aimed to identify both individual and community-level risk factors of childhood diarrheal in Ethiopia. Methods Ethiopian demography and health survey of 2016 data were used for the analysis. A total of 10,641 children aged 0-59 months were included in the analysis. A multi-level mixed-effect logistic regression model was used to identify both individual and community-level risk factors associated with childhood diarrheal. Result The incidence of childhood diarrheal was 12% (95%CI: 11.39, 12.63). The random effect model revealed that 67% of the variability of childhood diarrhea explained by individual and community level factors. From the individual-level factors, children aged 36-59 month (AOR = 3.166; 95% CI: 2.569, 3.900), twin child (AOR = 1.871; 95% CI: 1.390, 2.527), birth order 5 and above (AOR = 2.210, 95% CI: 1.721, 2.839), not received any vaccination (AOR = 1.197; 95% CI: 1.190,1.527), smaller size of child at birth (AOR = 1.303;95% CI: 1.130,1.504) and never breastfed children (AOR = 2.91;95%CI:2.380,3.567) associated with the higher incidence of childhood diarrhea. From the community-level factors, living in a rural area ((AOR = 1.505; 95%CI: 1.233, 1.836)), unprotected source of drinking water (AOR: 1.289; 95% CI: 1.060, 1.567) and availability of unimproved latrine facilities (OR: 1.289; 95% CI: 1.239, 1.759) associated with the higher incidence of childhood diarrhea. Besides, Children live in Afar, Amhara, Benishangul-Gumuz, Gambella, SNNPR and Dire Dawa regions had higher incidence of childhood diarrhea. Conclusion The incidence of childhood diarrhea was different from cluster to clusters in Ethiopia. Therefore, integrated child health intervention programs including provisions of toilet facility, access to a clean source of drinking water, educate parents about the importance of breastfeeding and vaccination have to be strongly implemented in order to reduce the high incidence of childhood diarrhea among children in Ethiopia.